Q: How do you solve this equation - 9 - 2x plus x equals - 13?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

5

Set up the equation and solve: 13 = 7 + s (next subtract 7 from each side of the equation to solve for s) 6 = s

Set up the equation and solve: x + 5 = -13 (next subtract 5 from each side of the equation to solve for x) x = -18

3h+13 = 7 3h = 7-13 3h = -6 h = -2

12 + 5 equals...

Related questions

5

Set up the equation and solve: 13 = 7 + s (next subtract 7 from each side of the equation to solve for s) 6 = s

If: 2a+13 = 5a+1 Then: a = 4

Set up the equation and solve: x + 5 = -13 (next subtract 5 from each side of the equation to solve for x) x = -18

+6

3h+13 = 7 3h = 7-13 3h = -6 h = -2

Dear Questioner its not able to solve two variables for one equation, give one more equation. Thanks

X +13 equals 22, X equals nine

12 + 5 equals...

x/2 = 13 - 6 so x/2 = 7 so x = 14

In the equation 3x plus 7 equals 13, x is equal to 2.

Yes that is correct